The use of alphanumeric display terminals : a thesis ... for the degree of Master of Arts in Computer Science at Massey University - Barrer, Patrick John (Massey University, 1975)
A functional description of alphanumeric display terminals is given and then the four main classes of interactive systems that use alphanumeric display terminals; enquiry/response systems, interactive programming systems, data entry and computer-aided instruction are briefly described. Some programming considerations where using alpha-numeric display terminals with interactive systems are mentioned and then a "virtual" alphanumeric display terminal is introduced. Finally as an example, the program entry phase of the Genisys system is described.
Keywords: Computer programming